Radiogenic nephropathy - Gotthardt, M. (Nuklearmedizin - NuclearMedicine, 2010)
Patient-individual dosimetric analyses are a useful tool in external beam radiotherapy (EBR) to protect patients from side effects such as radiogenic nephropathy. At this point in time, individual dosimetry is not used as a standard in patient treated with radiolabelled antibody fragments or polypeptides. The reasons are a number of problems, which make patient dosimetry more challenging than in EBR. While in EBR, the dose is distributed evenly in the organ and the organ volume can exactly be determined, in internal radiotherapy the tracer is not evenly distributed within the organ leading to a non-uniform dose distribution. In addition, the dose rate of the most commonly used radionuclides is lower than in EBR and the range of their radiation differ, so that the radiobiological effects are differing considerably in comparison to EBR. Conclusion: More complex models have to be used for clinical kidney dosimetry in internal radiotherapy.In this paper, we give a concise overview of the reasons for accumulation of radiotracers in the kidney, the most recent developments in kidney dosimetry, and approaches to reduce the kidney uptake of radiotracers in order to avoid radiogenic nephropathy.
Keywords: External beam radiotherapy; nephropathy; dosimetry